Hemorrhagic sucking blisters - Paloni, G.; Cutrone, M. (European Journal of Pediatric Dermatology, 2014)
Two otherwise healthy and full-term babies came to our observation for bullous hemorrhagic skin lesions involving in the first newborn the right hand and in the second one the left wrist (Fig. 1, 2). No other skin abnormalities were detected. Pregnancies had been uneventful and deliveries were uncomplicated. On physical examination the first newborn had a 5 mm in size, tense, blood blister on the dorsal aspect of the 3rd finger and, on the 4th finger, a 5 mm in size erosion and a 2.5 mm blood crust (Fig. 1); the second newborn had a 7 x 5 mm blister on the radial aspect of the wrist (Fig. 2). In both the newborns the rest of the physical examination was normal and the laboratory investigations ruled out maternal and/or neonatal infections. All lesions completely resolved after about 4 days without any treatment. The absence of lesions in other body regions, the timing of onset, and the rapid regression of the blisters in combination with the otherwise well appearance of the neonates were highly suggestive of hemorrhagic neonatal sucking blisters.